Analysis and Compensation of Nonlinear Impairments in Optical Fiber communication systems - BOUAFIA Fatma Batoul; DJERADI Bilal (University of Shahid Hama Lakhdar - El Oued, 2024)
Efficient and dependable communication systems are critical due to the increasing demand for high-bandwidth applications such as high-definition video streaming and cloud computing. Optical communication technologies have become the fundamental infrastructure of contemporary networks, facilitating the transfer of large quantities of data (such as high-definition video files) over long distances. Nevertheless, these systems are vulnerable to non-linear phenomena that result from the interaction between light and the optical fiber. The presence of non-linear effects can cause signal distortion, resulting in higher bit error rates (BER) and eventually degrading the performance of the system. The goal of this research project is to find ways to use digital backpropagation (DBP) to improve optical communication systems that have non-linear distortions. The objective is to reduce the negative impacts of non-linearity and enhance the efficiency of the system for transmitting high-speed data.تكتسي نظم الاتصالات الكفؤة والموثوقة أهمية حاسمة بسبب تزايد الطلب على التطبيقات ذات النطاق الترددي العالي مثل تدفق الفيديو العالي الوضوح والحوسبة السحابية. وقد أصبحت تكنولوجيات الاتصالات البصرية البنية الأساسية للشبكات المعاصرة، مما ييسر نقل كميات كبيرة من البيانات )مثل ملفات الفيديو العالية الوضوح( على مسافات طويل ة . ومع ذلك، فإن هذه النظم معرضة للظواهر غير الخطية الناجمة عن التفاعل بين الضوء والألياف البصرية. ويمكن أن يؤدي وجود آثار غير خطية إلى تشويه الإشارات، مما يؤدي إلى ارتفاع معدلات الخطأ بالبت، ويؤ دي في نهاية المطاف إلى تدهور أداء النظام . والهدف من هذا المشروع البحثي هو إيجاد سبل لاستخدام الارتجاع الرقمي لتحسين نظم الاتصالات البصرية التي تنطوي على تشوهات غير خطية. والهدف من ذلك هو الحد من الآثار السلبية لعدم الخط وتعزيز كفاءة نظام نقل البيانات العالية السرعة .
Master's theses: specializing in wired and non-wired communications
Keywords: optical coherence system; Kerr effects; DBP algorithm; nonlinearity compensation; نظام التماسك البصري، آثار كير، خوارزمية الانتشار الرقمي الخلف ي ، التعويض غير الخطي .